Motile cilia modulate neuronal and astroglial activity in the zebrafish larval brain - Percival P. D’Gama; Inyoung Jeong; Andreas Moe Nygård; Ahmed Jamali; Emre Yaksi; Nathalie Jurisch-Yaksi (Cell Reports)
Summary: The brain uses a specialized system to transport cerebrospinal fluid (CSF), consisting of interconnected ventricles lined by motile ciliated ependymal cells. These cells act jointly with CSF secretion and cardiac pressure gradients to regulate CSF dynamics. To date, the link between cilia-mediated CSF flow and brain function is poorly understood. Using zebrafish larvae as a model system, we identify that loss of ciliary motility does not alter progenitor proliferation, brain morphology, or spontaneous neural activity despite leading to an enlarged telencephalic ventricle. We observe altered neuronal responses to photic stimulations in the optic tectum and hindbrain and brain asymmetry defects in the habenula. Finally, we investigate astroglia since they contact CSF and regulate neuronal activity. Our analyses reveal a reduction in astroglial calcium signals during both spontaneous and light-evoked activity. Our findings highlight a role of motile cilia in regulating brain physiology through the modulation of neural and astroglial networks.